2015
DOI: 10.1038/ncomms8114
|View full text |Cite
|
Sign up to set email alerts
|

Effector lymphocyte-induced lymph node-like vasculature enables naive T-cell entry into tumours and enhanced anti-tumour immunity

Abstract: The presence of lymph node (LN)-like vasculature in tumors, characterized by expression of peripheral node addressin and chemokine CCL21, is correlated with T-cell infiltration and positive prognosis in breast cancer and melanoma patients. However, mechanisms controlling the development of LN-like vasculature and how it might contribute to a beneficial outcome for cancer patients are unknown. Here we demonstrate that LN-like vasculature is present in murine models of melanoma and lung carcinoma. It enables inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
213
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(228 citation statements)
references
References 65 publications
11
213
4
Order By: Relevance
“…A high density of extra‐tumoral and intra‐tumoral Th1 cells correspond with improved survival,71 where it is proposed that their local priming, possibly within ELFs, promotes antigen‐specific tumour responses 72, 73. In murine models of melanoma and lung carcinoma, the development of lymph node‐like vasculature allows naive T‐cell entry into tumours that delay tumour outgrowth 74. Therefore modulation of HEV development or function through targeting LT α 1 β 2 to the tumour or by inhibiting Treg activity may provide opportunities for novel immunotherapies.…”
Section: High Endothelial Venules At Elfsmentioning
confidence: 99%
“…A high density of extra‐tumoral and intra‐tumoral Th1 cells correspond with improved survival,71 where it is proposed that their local priming, possibly within ELFs, promotes antigen‐specific tumour responses 72, 73. In murine models of melanoma and lung carcinoma, the development of lymph node‐like vasculature allows naive T‐cell entry into tumours that delay tumour outgrowth 74. Therefore modulation of HEV development or function through targeting LT α 1 β 2 to the tumour or by inhibiting Treg activity may provide opportunities for novel immunotherapies.…”
Section: High Endothelial Venules At Elfsmentioning
confidence: 99%
“…This appears to be due to the presence in the tumors of vasculature resembling the high endothelial venules characteristic of lymph nodes. Through the expression of peripheral node addressins (PNAd) and CCL21 on the luminal endothelial surface, these blood vessels supported the extravasation of naive CD8 + T cells, which were subsequently activated in the tumor [48,49]. Thus, intratumoral expression of type I IFNs may even prompt tumor-infiltrating Batf3 DCs to cross-prime naive CD8 + T cells in the tumor, bypassing the need for migration to the draining lymph nodes.…”
Section: The Central Role For Type I Ifns and Batf3 Dcsmentioning
confidence: 99%
“…Tumors that are poorly infiltrated by effector T-cells may be poorly immunogenic due to a paucity of antigens. Consistent with this, we have observed that murine B16 melanoma tumors transfected to express ovalbumin as a strong neo-antigen are infiltrated by larger numbers of effector CD8 T-cells than the parental B16 line, which is poorly antigenic (71). Similar results have been reported for other implantable murine tumors (72).…”
Section: Determinants Of Cd8 T-cell Representation In Tumors Andsupporting
confidence: 78%